Optimization of coas doctor selection using PROMETHEE-based decision support system - M Salim; Sulistiawati Rahayu Ahmad; Yulanda Yunus (Geuthèë Institute, 2026)
The selection process of co-assistant (COAS) doctors in hospitals is a critical stage in ensuring the quality of healthcare services. However, in practice, this process is often conducted subjectively and lacks integration with a structured criteria-based system, which may lead to inconsistent and less accurate decision-making. However, existing studies still lack the implementation of integrated web-based decision support systems with validated ranking results, particularly in the context of COAS doctor selection. This study aims to optimize the selection process of COAS doctors by implementing a decision support system based on the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). The method is used to rank alternatives through a multi-criteria decision-making approach involving seven criteria, namely medical knowledge, service attitude, productivity, teamwork, discipline, honesty, and responsibility. The results show that the developed system is capable of generating objective candidate rankings, where the highest net flow value of 0.95 is achieved by the best candidate, indicating strong dominance over other alternatives. Furthermore, the implementation of the PROMETHEE method improves transparency and consistency in decision-making while reducing subjectivity compared to manual approaches. The web-based system also enhances efficiency through automated calculations and real-time data processing. Therefore, this study contributes to the development of multi-criteria decision support systems in the healthcare sector, particularly in providing a more objective, systematic, and efficient approach to COAS doctor selection.